Implementation of the Steam-Integrated Project-Based Learning Model to Improve IPAS Learning Activities and Outcomes - Nurul Qomariyah; Endah Andayani; Endang Surjati (BASICA, 2025)
This study was motivated by the fact that many students remain passive in the learning process and struggle to understand the topic “Daerahku Kebanggaanku,” resulting in suboptimal learning outcomes. The purpose of this research was to determine the effect of implementing a STEAM-integrated Project Based Learning (PjBL) model on improving students’ learning activities and outcomes in IPAS. The STEAM-integrated Project Based Learning model is a project-based instructional approach that can develop essential 21st-century skills, such as communication, teamwork, analytical thinking, and creativity. During the project process, students learn to collaborate, express ideas, and solve problems collectively. This approach not only prepares students for academic success but also equips them to become adaptive and innovative individuals in facing future challenges. This research employed a quantitative approach using a quasi-experimental design, with the research subjects being students of class VA at SDN Sukun 1 Malang City. The instruments used included learning outcome evaluation tests, learning activity questionnaires, and observation sheets. Data analysis was conducted using the paired-samples t-test in SPSS 26.00. The results of the study indicated a significant improvement in students’ learning activities and outcomes after the implementation of the STEAM-integrated Project Based Learning model. These findings demonstrate that the STEAM-integrated Project Based Learning model is effective for use in IPAS learning to enhance students’ learning activities and outcomes. The results of this study are expected to serve as a reference for teachers in implementing project-based learning models and to contribute to the development of contextual and engaging IPAS instruction.